(untitled) (Emancipação, 2022)
The study aimed to investigate elements and dimensions of professional resilience in workers of an institute for integral rehabilitation that help people with physical disabilities, victims of traffic accidents during the COVID-19 pandemic. The theoretical assumptions are based on the Bioecological Theory of Human Development and Froma Walsh model of Resilience in Families. With a qualitative design, semi-structured interviews were carried out and analyzed based on Grounded theory. The results identified three main categories: Reinvention of professional practices; Coexistence with emotional duality and innovative experiences. Overall, the categories showed important elements that promote processes of professional resilience based on the redefinition and transformations of perceptions, beliefs systems and practices of professionals who work in the risk context caused by COVID 19 Pandemic.